Analysis of Student Discipline Levels in the Face-to-Face Learning Process Post the Covid-19 Pandemic - Nasrullah, Muh; Lestari, Sri Ayu; Arhas, Sitti Hardiyanti (Universitas Negeri Makassar, 2023)
The emergence of Covid-19 has claimed so many lives. Globally, it brings change and impacts almost all aspects of life. In this research, the author wants to know the picture of student discipline in the face-to-face learning process after the COVID-19 pandemic in class XI IPS at SMAN 8 Maros. This research is qualitative research with data collection techniques consisting of observation, interviews, and documentation. There were 11 informants. The research results show that the level of student discipline in the face-to-face learning process after the COVID-19 pandemic in class XI IPS at SMAN 8 Maros is quite good. The results of this research are based on indicators of time discipline and action discipline where the majority of students are disciplined compared to those who are not disciplined by violating the rules set by the school. This research revealed that students' disciplined behavior when face-to-face learning resumed after previously being conducted online was quite good because interactions during learning went well without internet network interference